(untitled) (KULT_online, 2009)
The proceedings Horror and Aesthetic, published by Claudio Biedermann and Christian Stiegler, is concerned with the varied applications of a cross-medial aesthetic of horror, considered here – in interdisciplinary collaboration between students and noted academicians – over the course of 15 essays. Equal attention is given to horror motifs, the relationship between fiction and reality, and considerations of genre theory.